Comparative analysis of anthocyanin biosynthesis during fruit development in two Lycium species. Issue 4 (20th December 2013) - Zeng, Shaohua; Wu, Min; Zou, Caiyun; Liu, Xiaomin; Shen, Xiaofei; Hayward, Alice; Liu, Chunzhao; Wang, Ying
<x xml:space="preserve">Abstract</x> Dietary consumption of functional foods enriched in anthocyanins benefit for human health by protection against far‐ranging human diseases. Delphinidin‐derived anthocyanins (valuable as blue pigments and antioxidants) are accumulated specifically in the fruits of Lycium ruthenicum but not in the fruits of Lycium barbarum, suggesting the differences of anthocyanin biosynthesis between the two species. In this study, anthocyanin profiling confirmed that anthocyanins were increasingly accumulated during fruit ripening in L. ruthenicum, and sharply increased at full expanded mature fruit, while no anthocyanin were detected at any stage of L. barbarum fruit development. Several genes involved in anthocyanin biosynthesis were characterized in L. ruthenicum and L. barbarum fruits. Expression profiling of these genes during fruit development showed a significant positive correlation between transcript abundance and anthocyanin accumulation in L. ruthenicum fruit. Meanwhile, transcripts in L. barbarum fruit were either undetectable or were downregulated during fruit ripening, before increasing slightly in the final stages of maturation. In addition, the ratio of LrF3′5H/LrF3′H transcription showed a gradual increase before 6 days after breaker (DAB) and a sharp enhancement at 10 DAB. Our results suggest that the expression patterns of both regulatory and structural genes and the transcriptional ratio of branch‐node structural genes F3′5′H/F3′H may determine the phenotypic difference in anthocyanin biosynthesis between L. ruthenicum and L. barbarum fruits.